Orthopedic screws manufactured from lyophilized bovine bone: a procedure for implantation - Abedrabbo Hazbun, Anibal Faruk (2020)
The present work was based on manufacturing and testing of orthopaedic implant screws described in the ISO 5835: 1991 standard manufactured from lyophilized bovine bone, by comparison with the process commonly used by surgeons to implant commercial metal screws. This paper shows a procedure for implanting the lyophilized bone screws describing the neccesary steps: hydrate the screw in saline solution, avoiding any bending of the screw by the surgeon, prepare the thread on several occasions and clean the hole to insert the screw with the help of the medical torque wrench. This procedure was verified by implanting a screw as part of the fixation of fascia lata implants, for the extraarticular repair of anterior cruciate ligament rupture in a canine and a feline patient. The results showed a total osteointegration of the osseous implants used.